(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
This paper aims to identify the palaeographic traits of rock inscriptions in Cerdanya which are compatible with the dual system of Iberian writing, highlighting similarities and differences with the character forms used in neighbouring areas of the northeastern Iberian Peninsula and the south of France, between the 4th c. BCE and the middle of the 2nd c. BCE, when a Roman present is first documented in Cerdanya. Furthermore, archaeological and numismatic evidence is presented which sheds light on cultural and economic currents in Cerdanya, through which knowledge of writing arrived. It is concluded that, based on the evidence currently available, there are both palaeographic and archaeological reasons to consider the Empordà region the most influential for Iberian writing in Cerdanya.